Review of Food security and sociopolitical stability by Christopher B. Barrett - Alderman, Harold (American Economic Association, 2014)
Eighteen papers explore the relationship between food security and sociopolitical stability up to approximately 2025. Papers discuss food or consequences—food security and its implications for global sociopolitical stability; the future of the global food economy—scenarios for supply, demand, and prices; what we know about the climate of the next decade; the global land rush; global freshwater and food security in the face of potential adversity; managing marine resources for food and human security; crop technologies for the coming decade; livestock futures to 2020—how they will shape food, environmental, health, and global security; labor migration and food security in a changing climate; trade policies and global food security; food security and political stability—a humanitarian perspective; moral economics of food security and protest in Latin America; food security and sociopolitical stability in Sub-Saharan Africa; lessons from the Arab Spring—food security and stability in the Middle East and North Africa; food security and sociopolitical stability in Eastern Europe and Central Asia; food security and sociopolitical stability in South Asia; when China runs out of farmers; and food security and sociopolitical stability in East and Southeast Asia. Barrett is Stephen B. and Janice G. Ashley Professor of Applied Economics and Management, and International Professor of Agriculture in the Charles H. Dyson School of Applied Economics and Management, and Professor in the Department of Economics at Cornell University.